A inserção do assistente social no Programa Saúde da Família em Aracaju: os tempos de um movimento - Tavares, Maria Cecília (2009)
The reflection in this study focuses on the Health of the Family Program in Aracaju, as a Basic Attention policy, the insertion of the social workers in that program, and the changes occurred in the policy and in the work processes of these professionals, and in the evidences of change in the production of the healthcare. It also intends to find the conditions that favored or restrained the implementation of the PSF in Aracaju and conditioned the described scenarios; to reflect about the health policy that is being built in that municipality, considering the transformations demanded by the present health context, beyond subsidizing the debate about the inclusion, as a national policy, of the social workers in the Family Health Teams and of the condition of the social workers as health workers. The research is justified by the need of carrying out local studies that reveal the particularities about the form of the insertion of the social workers in the PSF in each specific context, in each local political project and the work processes outlined in them. The research, of qualitative nature, take one exploratory stage when I done interviews not structured with professionals of healthcare they have distinctions positions of local quarrel of professional healthcare, in 1980. Subsequently I done ten interviews guidance with professionals and eight social services, of each place of Aracaju, oriented to Oral History; I done bibliographical research; documental research; and workshops with all the social workers of the PSF, forty professionals. The analysis and interpretation with all this facts let me realize. the insertion of these social workers in PSF in Aracaju establish like one oh those unfold participation of those professionals in the Movement for Sanitary Reform in Sergipe, by the construction of SUS. The work process of these professionals wilt this insert show important changes, that it should be analyzed in biggest the context of production in health, of the processes operated